Victory in War : Foundations of Modern Military Policy - Martel, William C. (Cambridge Cambridge University Press, 2007)
For millennia, policymakers and statesmen have grappled with questions about the concept of victory in war. How long does it take to achieve victory and how do we know when victory is achieved? And, as highlighted by the wars against Afghanistan and Iraq, is it possible to win a war and yet lose the peace? The premise of this book is that we do not have a modern theory about victory and that, in order to answer these questions, we need one. This book explores historical definitions of victory, how victory has evolved, and how it has been implemented in war. It also subsequently develops the intellectual foundations of a modern pre-theory of victory, and discusses the military instruments necessary for victory in the twenty-first century using case studies that include US military intervention in Panama, Libya, Persian Gulf War, Bosnia/Kosovo, Afghanistan, and Iraq.
Include Notes and Index.
Foundations of Modern Military Policy.
Keywords: Military policy -- United States